THE CORRELATION BETWEEN SELF-ESTEEM AND SELF-DISCLOSURE IN STUDENTS ON INSTAGRAM - Anggi Tri Lestari Purba; Ayu Pratiwi Hasibuan (Sean Institute, 2023)
Instagram has been growing rapidly during the past decade. This makes researchers want to know how students' self-disclosure on Instagram. This study aims to see the correlation between self-esteem and self-disclosure in students on instagram. This research method uses quantitative methods. The population of this study was students who actively used instagram accounts and the sample of this study was 153 students. sampling technique using purposive sampling. Data collection uses a self-esteem scale and a self-disclosure scale measured using the likert scale form. Data analysis techniques used to product moment, the results showed that there was a significant correlation between self-esteem and self-disclosure in students. This result is evidenced by a correlation coefficient of rxy=0.462 with a signification value of p= 0.000 >0.05. Self-esteem of students has influenced the emergence of self-disclosure in Man Panyabungam students on Instagram.